Conflict Management Strategies to Improve School Performance in the Education Sector - Rahmat Muliana; Firman; Armaidi (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
Conflict is an inevitable part of social life that we all have to face from time to time, which can be a positive force for improvement in an educational institution. Conflict is an unavoidable phenomenon in the school environment, both among teachers, students, and other education personnel. Conflict that is not managed properly can have a negative impact on educational performance. This study aims to identify Conflict Management Strategies to Improve School Performance in Education. Through a qualitative-descriptive approach, data were obtained from the library collection using a descriptive approach. The library collection is extensive and diverse, containing books, articles and other materials on the topic of conflict management. Conflict management in educational institutions can help improve productivity, which shows that the application of strategies such as collaboration, compromise, and accommodation can create a conducive work environment, improve communication between individuals, and motivate the participation of all parties in achieving educational goals. The recommendation of this study is the importance of conflict management training for principals and teachers as an effort to improve the overall quality of school management. With proper conflict management, schools can create a harmonious and productive atmosphere, which ultimately supports the improvement of school performance in education.